2012
DOI: 10.1021/ja301326k
|View full text |Cite
|
Sign up to set email alerts
|

A Total Synthesis Prompts the Structure Revision of Haouamine B

Abstract: A concise asymmetric approach to the indeno-tetrahydropyridine core of the unusual alkaloid haouamine B allowed for an investigation of a biomimetic oxidative phenol coupling as a proposed biosynthetic step, and ultimately provided access to the published structure of the natural product. As a consequence of our synthetic studies, the structure of haouamine B has been revised.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 27 publications
1
31
0
Order By: Relevance
“…With key intermediate 59 in hand, the asymmetric synthesis of kainoid 60 was accomplished via a high-yielding sequence. The synthesis of iso-haouamine B is another example (Scheme 13) [39,40]. Structurally, this alkaloid, 64, consists of an indeno-tetrahydropyridine core fused to a highly distinctive 11-membered p-cyclophane ring.…”
Section: Chiral Pool: Serinementioning
confidence: 99%
“…With key intermediate 59 in hand, the asymmetric synthesis of kainoid 60 was accomplished via a high-yielding sequence. The synthesis of iso-haouamine B is another example (Scheme 13) [39,40]. Structurally, this alkaloid, 64, consists of an indeno-tetrahydropyridine core fused to a highly distinctive 11-membered p-cyclophane ring.…”
Section: Chiral Pool: Serinementioning
confidence: 99%
“…Thus, in the db C panel, two boryl linkers were first installed at its 3,11‐positions via an 8‐step synthetic process starting from a commercially available compound (Figure ). Bromoanisole 1 was iodized to furnish acetylene with aryl termini via Sonogashira coupling, and the subsequent four steps were performed without fully purifying the synthetic intermediates to afford 3 in 47 % yield. The diborylated db C precursor 4 for macrocyclization was then synthesized via ICl‐promoted cyclization, Mizorogi–Heck coupling and Miyaura borylation .…”
Section: Figurementioning
confidence: 99%
“…"However, Cope rearrangement of alkenylalkynylcyclopropanes has rarely been used, perhaps due to the formation of a reactive sevenmembered-ring allene, which may undergo rapid dimerization to give undesired products." He added: "By using easily prepared dienediynes as substrates, we found that the sevenmembered-ring allene intermediate, which was generated in situ by the Cope rearrangement of an alkenylalkynylcyclopropane, undergoes C(sp 3 ) -H activation of the side chain, instead of the undesired dimerization, to furnish the fused 5,7,6-tricyclic system. The present polycyclization reaction is a good example for step-economic construction of complex and challenging skeletons of important molecules from simple starting materials.…”
Section: Prof S Luomentioning
confidence: 99%